Study of material removal rate and electrode wear ratio for micro electrical discharge milling of AISI 420 and Stavax ESR - Mohammad, Yeakub Ali; Khan, Ahsan Ali; Hamzah, Munirah; Khalid, Nor Azura (Universiti Malaya, 2009)
This paper investigates micro electrical discharge (ED) milling for AISI 420 and Stavax ESR stainless steel using tungsten carbide electrode. For each of the materials, experiments have been conducted using the full factorial combination of gap voltage, capacitance and feed rate. Two responses material removal rate (MRR)and electrode wear ratio (EWR) are analyzed. Both MRR and EWR are found to be higher for AISI 420 compared to that of Stavax for the same machining parameters and environment. Empirical models are developed for the estimation of MRR and EWR. The empirical relationship shows that the feed rate and capacitance are the most important factors for MRR. However, gap voltage and capacitance are the main influential factors for EWR. Although the trend of relationship of MRR and EWR is found to be similar for both materials, the level of influence is found to be significantly different. For multiple optimization of MRR and EWR, the machining parameters are determined analytically and verified experimentally. The optimized values of gap voltage and feed rate are 100 V and 6 μm.s-1 for both materials. However, the optimized capacitance is 8.55 nF and 1 nF for AISI 420 and Stavax ESR respectively. The verification experiment shows that the measured values of MRR and EWR are within 5-10% of the predicted values. For the Stavax ESR the MRR and EWR are found lower than that for AISI 420. The possible reasons of these lower MRR and EWR are discussed.